2020
DOI: 10.3389/fpsyg.2020.02162
|View full text |Cite
|
Sign up to set email alerts
|

Financial Socialization, Childhood Experiences and Financial Well-Being: The Mediating Role of Locus of Control

Abstract: The present study evaluates an empirical model of financial well-being (FWB) based on early childhood consumer experiences (ECCE) and financial socialization (FS). FWB is the overall satisfaction with one’s current financial situation, and that plays a vital role in the overall success and helps to overcome psychological health issues among adults. The results of the study suggested that ECCE has a significant direct effect on the FWB among adults. Moreover, FS agents such as peers harm the financial well-bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 45 publications
6
42
1
3
Order By: Relevance
“…While the locus of control is considered a central component of well-being (Spector et al, 2002), there are a limited number of studies which have explored the relationship between locus of control and financial well-being (Cobb-Clark et al, 2016;Mokhtar and Husniyah, 2017). In the context of personal finance, research indicates that the locus of control relates to financial satisfaction and savings, where people with a higher level of control are more satisfied with their financial status (Ullah and Yusheng, 2020) and are in more control over their savings.…”
Section: Psychological Beliefs and Financial Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…While the locus of control is considered a central component of well-being (Spector et al, 2002), there are a limited number of studies which have explored the relationship between locus of control and financial well-being (Cobb-Clark et al, 2016;Mokhtar and Husniyah, 2017). In the context of personal finance, research indicates that the locus of control relates to financial satisfaction and savings, where people with a higher level of control are more satisfied with their financial status (Ullah and Yusheng, 2020) and are in more control over their savings.…”
Section: Psychological Beliefs and Financial Wellbeingmentioning
confidence: 99%
“…This would imply that the different types of locus of control should be investigated separately (Brewin and Shapiro, 1984). Furthermore, past research has suggested that when examining personal financial behaviour and financial well-being, internal locus of control is more relevant (Jorgensen et al, 2017;Ullah and Yusheng, 2020). Therefore, this study focused on the internal locus of control, as it is arguably more appropriate to investigate a personal, psychosocial perspective.…”
Section: Psychological Beliefs and Financial Wellbeingmentioning
confidence: 99%
“…According to Ullah and Yusheng [44], financial socialization includes the development of standards, values, norms, and attitudes, rather than just related to managing money. As described by Asad et al [4] financial socialization has much importance in making sound financial decisions.…”
Section: Family Financial Socializationmentioning
confidence: 99%
“…To do so, we propose a model of FS and ECCE on FCB and their connection with FWB. Although developmental studies examined these factors (Sabri, 2011 ; Drever et al, 2015 ; Netemeyer et al, 2018 ; Rea et al, 2019 ; Lanz et al, 2020 ; Mubeen et al, 2020 ; Sabri et al, 2020 ; Ullah and Yusheng, 2020 ), they applied other combination of variables to study FWB.…”
Section: Introductionmentioning
confidence: 99%